Propuesta de un sistema de prevención de riesgos laborales basado en la norma iso 45001:2018; en el “Cuerpo de bomberos municipal del cantón Quevedo - Litardo Romero, Alisson Milena (2022)
The Municipal Fire Department of Canton Quevedo is a public institution dedicated to disaster relief and emergency response, offering various services to help the community. Therefore, they are exposed to different risk factors, creating the need for adequate management of occupational risks. For the development of this research, questions were raised to develop the proposal of a Risk Prevention System based on ISO 45001:2018, which are: What is the current situation regarding Occupational Risk Prevention in the Municipal Fire Department of Canton Quevedo, What are the requirements of ISO 45001 applicable to CBMCQ for proper compliance in terms of Occupational Safety and Health, Will it be possible to develop a proposal of the Occupational Risk Prevention System based on ISO 45001 for CBMCQ, Will it be possible to develop a proposal of the Occupational Risk Prevention System based on ISO 45001 for CBMCQ. Therefore, inductive, deductive and bibliographic methods were used to contribute to the development of this research. An initial situation status was made to know the level of compliance of the institution in human talent management, document management, occupational risk prevention management, natural hazards and anthropic risks, occupational health management and permanent services, applying the checklist of compliance with legal regulations on Occupational Risk Prevention established by the Ministry of Labor. Afterwards, the requirements of the ISO 45001 standard applicable to the Quevedo Municipal Fire Department were determined, indicating whether or not the institution complies with the aforementioned standard. Finally, the CBMCQ's Occupational Risk Prevention System was structured by means of documentation, procedures, instructions, records and matrices to be applied later. KEY WORDS: Organization, Improvement, Industrial, Management, Safety